Comparing the reinforcing efficacy of tokens and primary reinforcers. Issue 3 (12th January 2020) - Bonfonte, Stephanie A.; Bourret, Jason C.; Lloveras, Lindsay A.
Abstract : Token economies are one of the most commonly used behavior‐analytic interventions. Despite literature supporting the use of tokens as tools for behavior change, little is known about the efficacy of tokens compared to that of the items for which they are exchanged. Results of previous research comparing the reinforcing efficacy of tokens and primary reinforcers have shown that both produce similar effects on responding. However, published findings have been confounded given the inclusion of primary reinforcers in the token‐reinforcer test conditions. In this study, we established novel tokens as reinforcers. We then conducted a conditioned‐reinforcer assessment using a tandem control to ensure that the tokens functioned as reinforcers. We used progressive‐ratio schedules to compare the reinforcing efficacy of the tokens to high‐ and low‐preference edibles that were also used as backup reinforcers. For both participants, we found that high‐preference primary reinforcers maintained higher response frequencies than did tokens.